Sexual Abuse of Children in the 1980s : Ten Essays and an Annotated Bibliography - Schlesinger, Benjamin (Book collections on Project MUSE., 1986)
Increasing public concern has focused in recent years on the issue of sexual abuse of children. In addressing this difficult issue Benjamin Schlesinger brings together ten new essays from authorities in the field and an annotated bibliography of writings on the subject since 1980.